1991
DOI: 10.1002/ijc.2910480111
|View full text |Cite
|
Sign up to set email alerts
|

Selective homing of phenotypically lytic cells within nasopharyngeal carcinoma biopsies: Numerous CD8‐ and CD16‐positive cells in the tumor

Abstract: We present a comparative analysis of cell-mediated immunity between circulating lymphocytes and tumor-infiltrating lymphocytes (TlL) from patients with nasopharyngeal carcinoma (NPC). Phenotypic analysis using a panel of monoclonal antibodies (MAbs) to define lymphocytic subsets has revealed a selective homing of phenotypically lytic cells such as CD8and CDIdpositive cells, but a low percentage of macrophages when compared to PBL of NPC patients. Also, PBL and TIL contain an equivalent percentage of activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Similarly, the percentages of the tumor-infiltrating T cells were also reduced, as demonstrated using another NPC-PDX ( Figure S4A-K). Consistent with the primary tumor, T cells were also the major immune cell subset in the NPC-PDX, albeit the tumor-infiltrating macrophages and NK cells accounted for around 5% in our model [28,29]. Hence, the expressions of immune checkpoint receptors on the cytotoxic T lymphocytes were further examined.…”
Section: Tumor-infiltrating T Cells Display Exhausted Phenotypesmentioning
confidence: 91%
“…Similarly, the percentages of the tumor-infiltrating T cells were also reduced, as demonstrated using another NPC-PDX ( Figure S4A-K). Consistent with the primary tumor, T cells were also the major immune cell subset in the NPC-PDX, albeit the tumor-infiltrating macrophages and NK cells accounted for around 5% in our model [28,29]. Hence, the expressions of immune checkpoint receptors on the cytotoxic T lymphocytes were further examined.…”
Section: Tumor-infiltrating T Cells Display Exhausted Phenotypesmentioning
confidence: 91%
“…The appearance of a malignant process producing several immunogenic viral proteins within a context of local inflammation and heavy leukocytic infiltration is one major paradox of NPC pathogenesis. Moreover, another important biologic feature of NPC is the presence of a massive population of tumor-infiltrating lymphocytes (TILs) in the primary tumor [6-8]. Our previous study indicated that the frequencies of different TIL subsets, including CD8 + , FOXP3 + , and IL-17-producing TILs, have prognostic value in NPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large number of tumor infiltrating lymphocytes (TIL) are found around the NPC tumor tissues [5-8]. The majority of the cells in the tumor are reactive and consist predominantly of T cells with variable numbers of other inflammatory cells [9]. The presence of TIL correlates with an better prognosis in patients with several types of cancer, and each T lymphocyte subset has a unique role in the antitumor response [10-14].…”
Section: Introductionmentioning
confidence: 99%